Kedudukan Peserta Program Pendidikan Dokter Spesialis dalam Hak Pengupahan sebagai Tenaga Medis - Herdiasti Anggitya Dwisani (Syntax Corporation Indonesia, 2024)
Doctors are a professional that is needed by society and is a profession that carries a high level of responsibility. To support the capabilities of health workers, medical education has a Specialist Doctor Education Program and a Subspecialist Doctor Education Program. This is intended so that the needs of health workers, especially doctors who have certain health qualifications, can be met. This journal examines further the rights that participants in the Specialist Doctor Education Program and Subspecialist Doctor Education Program should have in carrying out their education. Through a normative juridical approach with qualitative analysis methods, this research explores the existing regulatory framework, identifies gaps in implementation, and formulates comprehensive regulatory solutions. The research results reveal that there is a legal void regarding the status of participants in the Specialist Doctor Education Program and Subspecialist Doctor Education Program, whether as interns or as workers. This research recommends the establishment of a special regulatory framework that regulates the determination of the status of participants in Specialist Medical Education Programs and Subspecialist Medical Education Programs..